Nutrition support for patients in the intensive care unit. Issue 960 (6th October 2005) - Griffiths, R D; Bongers, T
Abstract : Enteral nutrition (EN) is the mainstay of nutrition delivery within intensive care seeking to capitalise on its benefits for the gastrointestinal tract and associated immune system, but this has brought new challenges in delivery to the sick. The hoped for benefit has led to the mistaken belief by some that parenteral nutrition (PN) is no longer required. However, a greater appreciation of the risks of EN delivery in the sick patient combined with improvements in PN formulation and use help explain why PN is not as risky as some have believed. Real outcome benefits have been described with the new glutamine containing PN formulations. PN remains important in the presence of gastrointestinal feed intolerance or failure.